Dasatinib Inhibits Lung Cancer Cell Growth and Patient Derived Tumor Growth in Mice by Targeting LIMK1 - Zhang, Man; Tian, Jie; Wang, Rui; Song, Mengqiu; Zhao, Ran; Chen, Hanyong; Liu, Kangdong; Shim, Jung-Hyun; Zhu, Feng; Dong, Zigang; Lee, Mee-Hyun (Frontiers in Cell and Developmental Biology, 2020)
Lung cancer is a leading cause cancer-related death with diversity. A promising approach to meet the need for improved cancer treatment is drug repurposing. Dasatinib, a second generation of tyrosine kinase inhibitors (TKIs), is a potent treatment agent for chronic myeloid leukemia (CML) approved by FDA, however, its off-targets and the underlying mechanisms in lung cancer have not been elucidated yet. LIM kinase 1 (LIMK1) is a serine/threonine kinase, which is highly upregulated in human cancers. Herein, we demonstrated that dasatinib dose-dependently blocked lung cancer cell proliferation and repressed LIMK1 activities by directly targeting LIMK1. It was confirmed that knockdown of LIMK1 expression suppressed lung cancer cell proliferation. From the in silico screening results, dasatinib may target to LIMK1. Indeed, dasatinib significantly inhibited the LIMK1 activity as evidenced by kinase and binding assay, and computational docking model analysis. Dasatinib inhibited lung cancer cell growth, while induced cell apoptosis as well as cell cycle arrest at the G1 phase. Meanwhile, dasatinib also suppressed the expression of markers relating cell cycle, cyclin D1, D3, and CDK2, and increased the levels of markers involved in cell apoptosis, cleaved caspase-3 and caspase-7 by downregulating phosphorylated LIMK1 (p-LIMK1) and cofilin (p-cofilin). Furthermore, in patient-derived xenografts (PDXs), dasatinib (30 mg/kg) significantly inhibited the growth of tumors in SCID mice which highly expressed LIMK1 without changing the bodyweight. In summary, our results indicate that dasatinib acts as a novel LIMK1 inhibitor to suppress the lung cancer cell proliferation in vitro and tumor growth in vivo, which suggests evidence for the application of dasatinib in lung cancer therapy.